BIOACCMULATION OF HEAVY METALS MERCURY (HG), LEAD (PB), AND CADMIUM (CD) IN WATER AND RIVER CATFISH (HEMIBAGRUS NEMURUS) IN THE CITARUM DOWNSTREAM - Edrea Muhammad, Farrel
The Citarum is an ancient river that has its headwaters in Mount Wayang, Bandung Regency (1,700 m above sea level), this river flows for 297 kilometers to one of the north coasts of Java Island in Karawang Regency. Industrial activities in the downstream Citarum watershed have caused heavy metal content in the water to become high and affect organisms living in the waters, one of which is Catfish. Heavy metal contamination of Catfish can cause adverse effects on humans who eat it. This study aims to analyze the heavy metal content of Lead (Pb), Cadmium (Cd) and Mercury (Hg) in water and Catfish in the Lower Citarum River basin, and to determine the status and quality of the water. Based on the land use in the area passed by the river, five locations were selected purposively: Curug Dam, Walahar Dam, Teluk Jambe, Tanjung Pura, and Rengas Dengklok. Water samples were taken from three points located on the right bank of the river, the middle of the river and the left bank of the river. The depth of water sampling is half of the total depth at the sampling point. Sampling was done in the morning (07.00) and afternoon (16.00) as much as 1 liter and stored in HDPE plastic bottles. Measurement of physical and chemical parameters of water was carried out directly in the field and laboratory. Field measurements include temperature, pH, depth, brightness, current speed and dissolved oxygen (DO) content. Laboratory measurements include Total Solid Suspended (TSS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), heavy metal levels (Hg, Pb, and Cd) carried out at the Central Unpad Laboratory and Perum Jasa Tirta II Laboratory. Water sample preparation was conducted according to the Standard Method for the Examination of Water and Wastewater 23rd Edition. The Catfish samples were taken using stocking nets and fishing rods from 5 stations assisted by local fishermen, fish sampling efforts lasted for 14 days from June 20 to July 4, 2022. The Catfish samples were then stored and preserved in a coolbox. The Fish sample preparation was conducted according to USGS Test Method B9001-95. Data were analyzed using the STORET method, heavy metal accumulation analysis (BAF), T test, PCA, Manova test, and Pearson Correlation analysis. In the metal analysis results, Catfish had a higher concentration of Hg metal (1.26 mg/kg) than Pb metal (0.31 mg/kg) and Cd (0.01 mg/kg). The concentration of Hg and Pb metals in the body of Catfish has exceeded the quality standards, but the Cd metal in the body of Catfish still meets the quality standards. Based on BAF calculation, Catfish accumulated Hg metal up to 4.9 times from water, Pb metal up to 4.1 times and Cd metal up to 4.3 times from water. Conditions at the five stations, have poor quality and have been heavily polluted, station 4 has the highest or worst score and stations 1 and 3 have the lowest total score.